2020
DOI: 10.1186/s13034-020-0309-9
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone use disorder and future time perspective of college students: the mediating role of depression and moderating role of mindfulness

Abstract: Background: Smartphone use disorder (SUD) of college students has drawn increasing attention. Although future time perspective (FTP) may be an important protective factor for individual SUD, the moderating and mediating mechanisms underlying this relationship remain unknown. We tested the individual roles of depression and mindfulness as moderators of this relationship. Methods: A cross-sectional study was conducted in two colleges in Shandong and Chongqing in China using a sample of 1304 college students recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Subjective wellbeing is defined as a person's evaluative response to his or her life and can be divided into cognitive components, such as life satisfaction and affective components, i.e., happiness. This paper used Stubbe et al's SWB scale, which also contains five questions measuring individuals' life satisfaction and happiness (Nie and Ma, 2020 ; Zhang et al, 2020 ). The respondents rated the scale on a Likert scale from “strongly disagree” (assigned a score of 1) to “strongly agree” (assigned a score of 5), with higher scores indicating higher SWB.…”
Section: Methodsmentioning
confidence: 99%
“…Subjective wellbeing is defined as a person's evaluative response to his or her life and can be divided into cognitive components, such as life satisfaction and affective components, i.e., happiness. This paper used Stubbe et al's SWB scale, which also contains five questions measuring individuals' life satisfaction and happiness (Nie and Ma, 2020 ; Zhang et al, 2020 ). The respondents rated the scale on a Likert scale from “strongly disagree” (assigned a score of 1) to “strongly agree” (assigned a score of 5), with higher scores indicating higher SWB.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies reported the negative relationship between depression and self-efficacy, and the influence of depression on individual performance. Individuals with high levels of depression tend to have low levels of motivation ( Xiao et al, 2021 ) and self-efficacy ( King, Wu, & Niranjan, 2014 ; Melo et al, 2021 ), less control of their cognition and behaviors ( Zhang et al, 2020 ), and poor performance ( Son & Won, 2017 ). Also, depression contributes to weaken self-regulation, often influencing the ability to organize time and study environment, and to regulate emotion and effort, which may lead to decreases in learning engagement and performance ( Hinkson Jr. et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, scientists have started to use the terms disorde r or disordered use also in relation to other forms of addictive media technology use, like, for example, social media (use) disorder [e.g., ( 19 , 20 )]. Following Sha et al ( 21 ) and others [e.g., ( 22 , 23 )] we will use the term Smartphone Use Disorder (SmUD) as a synonym for uncontrolled, addictive smartphone use in the following. As suggested by Montag et al ( 24 ), we will abbreviate the term with SmUD because SUD could easily be misunderstood as an acronym for Substance Use Disorder.…”
Section: Introductionmentioning
confidence: 99%